Effectiveness of Transversus Abdominis Plane Block for Postoperative Analgesia in Obstetric Cases Undergoing Caesarean Section - Pradhan, Roshan; Mishra, Seema Kumari; Rajbanshi, Lalit Kumar; Khanal, Kanak; Arjyal, Batsalya; Pokharel, Hanoon P (Birat Journal of Health Sciences, 2019)
Introduction: Transversus abdominis plane (TAP) block is a regional anesthesia that involves the infiltration of local anesthetic in between the internal oblique and transversus abdominis muscle plane. This block provides post-operative analgesia and reduces the requirement of opioids consumption. Objective: To assess the effectiveness of TAP block in providing postoperative analgesia in women undergoing caesarean section. Methodology: This was a hospital based prospective, comparative, cross sectional study conducted in 70 patients from 17th September 2018 to 17th February 2019 undergoing caesarean section under spinal anesthesia. Patients were divided into two groups. Group A patients received TAP block with 0.5% Ropivacaine versus Group B patients received injection paracetamol 1gm intravenous every 8 hourly as a standard and routine analgesic. At the end of the surgery, TAP block was performed by anesthesiologist and assessment of postoperative pain using a visual analogue pain score at every 1 hour, 3 hour, 6 hour, 12 hour and 24 hour by trained staffs at postoperative ward. Then, depending upon the severity of the pain injection fentanyl 1mcg/kg intravenous was given as rescue analgesia. Short assessment of patient satisfaction (SAPS) score was also assessed 24 hours postoperatively. Results: Compared to control group, in women who received TAP block, there was statistically significant reduction in pain at 3 hr, 6 hr, 24 hrs. However at 12 hrs there was no significant difference in the pain score. The cumulative fentanyl requirement was also significantly less in the TAP block group at all the time points. Conclusion: The TAP block provided highly effective postoperative analgesia following caesarean section and reduces the fentanyl requirement in the first 24 hour.